Yeasticidal activity of chemical disinfectants and antiseptics against Candida auris. Issue 4 (December 2017) - Moore, G.; Schelenz, S.; Borman, A.M.; Johnson, E.M.; Brown, C.S.
Summary: Candida auris appears to be transmitted readily between patients, yet information regarding the efficacy of environmental disinfection and skin decolonization is lacking. A quantitative suspension test (EN 13624:2013) was used to evaluate the yeasticidal activity of different chemical disinfectants and antiseptics against C. auris and Candida albicans . When tested in suspension, both a chlorine-based disinfectant and iodine-based skin antiseptic were effective against C. auris, suggesting that their use could reduce environmental contamination and skin colonization, respectively, if applied appropriately. Chlorhexidine-based products may also be effective. However, in this study, activity depended on formulation, specifically the presence of isopropyl alcohol.